MORPHOLOGICAL CHANGES IN CERTAIN SUBJECTS IN THE UZBEK LANGUAGE - Salaeva Gulasal Gayratbek kizi (INTERNATIONAL JOURNAL OF RESEARCH IN COMMERCE, IT, ENGINEERING AND SOCIAL SCIENCES ISSN: 2349-7793 Impact Factor: 6.876, 2023)
After the transition of the Uzbek language to the graphic system, and especially in the later periods, the spelling of the acquired words and the appearance of their morphological structure began to be as close as possible to the source language, and stabilized significantly.